The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/micr.30810
|View full text |Cite
|
Sign up to set email alerts
|

Using the modified frailty index to predict negative outcomes in free‐flap breast reconstruction: A National Surgical Quality Improvement Project‐based study

Abstract: Background: Post-mastectomy free-flap breast reconstruction is becoming increasingly common in the United States. However, predicting which patients may suffer complications remains challenging. We sought to apply the validated modified frailty index (mFI) to free-flap breast reconstruction in breast cancer patients and determine its utility in predicting negative outcomes. Methods:We conducted a retrospective study using National Surgical Quality Improvement Project (NSQIP). All patients who had a CPT code of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Other studies have also evaluated frailty as another parameter for a possible perioperative risk stratification. It was found that the determination of frailty indices or scores may be a more helpful indicator for flap reconstruction, e.g., in the head and neck region or in breast reconstruction, than age itself [ 12 , 37 , 38 , 39 ]. Thus, higher frailty scores have been found to be associated with a negative outcome after free flap surgery [ 39 ], and that frail patients benefit from being cared for in the intensive care unit after flap surgery [ 12 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also evaluated frailty as another parameter for a possible perioperative risk stratification. It was found that the determination of frailty indices or scores may be a more helpful indicator for flap reconstruction, e.g., in the head and neck region or in breast reconstruction, than age itself [ 12 , 37 , 38 , 39 ]. Thus, higher frailty scores have been found to be associated with a negative outcome after free flap surgery [ 39 ], and that frail patients benefit from being cared for in the intensive care unit after flap surgery [ 12 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 5‐mFI score is a valuable prognostic tool for post‐surgical morbidity and mortality that has been adapted for multitude of specialties (Balla et al, 2019; Chimukangara et al, 2017; Lee et al, 2020; Runner et al, 2017; Segal et al, 2018; Traven et al, 2019; Wilson et al, 2018; Yagi et al, 2019). In recent years, this metric has been rapidly drawing attention as a tool for pre‐operative risk stratification and patient counseling and its use has bled into the realm of plastic surgery (Jain et al, 2021; Lee et al, 2020). While previous literature has highlighted the influence of individual risk factors for 30‐day complications after LE free‐flap reconstruction, the use of 5‐mFI as a comprehensive predictive tool in this arena has not been previously described.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the mFI‐5 has been studied for predicting negative outcomes in microsurgical reconstruction (Jain et al, 2021; Mascarella et al, 2022). Jain et al (2021) conducted a retrospective analysis using the NSQIP database, focusing on 11,852 breast cancer patients who underwent free‐flap breast.…”
Section: Discussionmentioning
confidence: 99%